1974
DOI: 10.1044/jshr.1703.455
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Individual Difference in the Spoken Syntax of School Children

Abstract: Language produced by 180 children (aged five through 13 years) on a story-telling task was analyzed in terms of 57 variables (part-of-speech frequencies and proportions, syntactic elaboration indexes, and constructional variety measures). A factor analysis revealed five dimensions of syntactic usage: general fluency, embeddedness, finite verb structure, noun phrase structure, and qualified speech. The embeddedness dimension was the only one with a sizable relation to age and is interpretable in terms of a deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Thus, after the age of six to seven, rather than producing new structures (for the most part mastered), children are facing a progressive increase in the complexity of produced utterances, with a deeper degree of embedding (Delage, 2008;Delage & Tuller, 2010;Hamann & Tuller, 2014). Therefore, Hass and Wepman (1974), among others, underlined a significant age effect on the number of embedded clauses measured with spontaneous language samples produced by 167 English-speaking children aged three to thirteen (see also Hamann et al, 2007;Leadholm & Miller, 1992;Loban, 1976;Reilly, Losh, Bellugi, & Wulfeck, 2004;or Soares, 2006, who highlighted the same progression in the complexity of produced utterances with age).…”
mentioning
confidence: 92%
“…Thus, after the age of six to seven, rather than producing new structures (for the most part mastered), children are facing a progressive increase in the complexity of produced utterances, with a deeper degree of embedding (Delage, 2008;Delage & Tuller, 2010;Hamann & Tuller, 2014). Therefore, Hass and Wepman (1974), among others, underlined a significant age effect on the number of embedded clauses measured with spontaneous language samples produced by 167 English-speaking children aged three to thirteen (see also Hamann et al, 2007;Leadholm & Miller, 1992;Loban, 1976;Reilly, Losh, Bellugi, & Wulfeck, 2004;or Soares, 2006, who highlighted the same progression in the complexity of produced utterances with age).…”
mentioning
confidence: 92%
“…Après 6-7 ans, plus que l'apparition de nouvelles structures (déjà quasi toutes maîtrisées), on assiste davantage à une augmentation progressive de la complexité des énoncés, avec notamment un degré d'enchâssement plus profond (Delage, 2008). Ainsi, parmi d'autres, Hass & Wepman (1974) ont souligné la présence d'un effet d'âge significatif sur le taux de subordination mesuré à partir d'échantillons de langage spontané dirigé (récit) chez 167 enfants anglophones entre les âges de 3 et 13 ans (voir aussi Loban, 1976 ;Leadholm & Miller, 1992 ;Scott, 2003 ;Reilly et al, 2004ou Hamann et al, 2007 qui montrent la même progression avec l'âge de la production d'énoncés complexes). Suivant notamment Jakubowicz (2005Jakubowicz ( , 2011, nous postulons l'hypothèse d'un lien direct entre cette progression dans l'utilisation de la syntaxe complexe et le développement des capacités de mémoire de travail.…”
Section: Complexité Syntaxiqueunclassified
“…Accordingly, the hypothesis was formed that college students with learning disabilities may continue to experience deficits in the knowledge of the distributional rules for personal and reflexive pronouns. Hass and Wepman (1974) observed that the factor embeddedness in spoken syntax related clearly to syntactic abilities which changed in a positive direction with age. They analyzed the spoken syntax of school children aged 5 to 13 years old.…”
mentioning
confidence: 89%